The relationship of farm surroundings and local infestation pressure to pest management in cultivated Passiflora species in Colombia? - Wyckhuys, Kris A.G.; López Acosta, F.J.; Rojas, M.; Ocampo, J (Informa UK Limited, 2010)
In South America, lance flies (Diptera: Lonchaeidae) are key pests of cultivated Passiflora spp. (passionfruit; Violales: Passifloraceae), but little is known about how to control these pests in Passiflora orchards. Here, we relate agro-ecological knowledge and pest management of Colombian Passiflora producers to local Lonchaeid infestation levels and farm surroundings. For this purpose, we carried out a nationwide survey of producers of purple, sweet and yellow passionfruit. Approximately 60% farmers (n = 124) reported Diptera as herbivores, with 4 43% explicitly referring to Lonchaeidae, while 90.5% of all farmers relied on calendar-based insecticide sprays for their control. Supplementary management options included use of baited traps for lonchaeid control and sanitary practices. Farmers experimented to a high extent with different products as bait in McPhail traps. In all, 15 potential baits were used, of which sugarcane molasses and protein hydrolysate proved popular. Farm surroundings and crop type affected farmers' use of baited traps, with traps commonly used in purple passionfruit orchards and employed in 100% farms surrounded by coffee plantations. Insecticide application frequency was positively correlated with lonchaeid infestation in fruits, but not in floral buds or flowers. For certain Passiflora crops, use of baited traps and trap density were related to infestation pressure. In conclusion, lonchaeid infestation pressure and farm surroundings affect Passiflora growers' pest management, respectively by creating a direct need for pest management intervention or by exposing farmers to distinct sets of pest management alternatives. This study sheds light on Passiflora farmers' agro-ecological knowledge, and it identifies low-cost, locality-specific pest management options. Hence, our findings may be valuable for future design and implementation of IPM programmes.